What does a photovoice project contribute to the analysis of heritage representations? A critical analysis of the "Places in Me" project with the Khwe and !Xun communities in Platfontein - (:unkn) unknown (My University, 2024)
In the proposed talk, we will critically assess a photovoice project co-conducted between researchers and San communities in Platfontein in 2022 and that resulted in an exhibition (opening July 2023). This project emerged from a participatory and collaborative approach involving a multidisciplinary team of researchers (ANR COSMO-ART project), South African academics, local heritage, and cultural institutions (Sol Plaatje University, McGregor Museum), and two local NPOs, SANCD and SASDO.The project, carried out in Platfontein (Northern Cape, South Africa), involved the Khwe and !Xun communities living near the Wildebeest Kuil rock art site. The tourism industry often emphasises the spatial proximity between these two communities and rock art sites to justify their relationship. Our work sought to investigate the state of this relationship and evaluate the extent to which the rock art sites truly represent heritage for these two San communities. To achieve this, we implemented a photovoice process. Collaborating with the local NPOs, community members were invited to participate in the project and tasked with taking photos of places they deemed significant. Individual interviews based on the photos were then conducted with each participant.Surprisingly, none of the participants took pictures of the rock art site, indicating a significant disconnect between the narratives propagated by tourism discourses and the actual state of the communities’ relationship with the rock art site.At the same time as the photovoice process was taking place, an exhibition initiative was underway, aiming to showcase what the participants defined as their heritage, from their point of view. Selected photographs and excerpts from interviews were paired for display. The final exhibition consisted of 21 kakemonos accompanied by a booklet with texts in Xuntali, Khwedam, Afrikaans, and Setswana. In addition, a QR code system facilitated access to audio recordings of the selected
Keywords: African Research